Initial growth of Eugenia stipitata, Inga spectabilis, and Inga edulis in Napo, Ecuador - Abril Saltos, Ricardo Vinicio; Ruiz Vázquez, Tomás Elías; Alonso Lazo, Jatnel; Cabrera Murillo, Génova Marjorie; Meric, Olivier Angel (Agronomía Mesoamericana, 2018)
Agriculture has been one of the causes of deforestation, causing environmental impact and soil degeneration, which leads to lower income earned by farmers; hence the need to implement agroforestry systems .This research aims to describe fromthe initial growth of Eugenia stipitata, Inga edulis, and Inga spectabilis to 320 days after emergence. The study took place at the Amazon Research and Conservation Center of the Amazonas State University, during 2014 and 2015. The growth process was evaluated in regards to plant height, stem diameter, number of leaves, and branch length. Plant height and stem diameter were compared over time applying variance analysis. Precipitation was also compared to analyze whether its variations had a direct influence on plant growth. The linear and polynomial models fitted better for thespecies regarding plant height and sprout diameter. Predominance of green leaves compared to yellow and dry ones, as branch length showed significant differences over all the sampling periods. The two-way analysis of variance showed significant differences in the correlation between age and precipitation over plant height and stem diameter. The outcomes led to conclude that Eugenia stipitata had a lower growth than both Inga edulis and Inga spectabilis. Branch production and growth and the number of leaves were also important elements of the growth process.